Desenvolvimento de um sistema de controle e interfaceamento para um macroindentador portátil para avaliação de propriedades mecânicas de dutos baseado em tecnologias DSP e Wireless - Sousa, Jeovane Vicente de (2011)
Obtaining mechanical properties of pipelines has fundamental importance to optimize their use. This fact is more relevant in lines where documentation is not precise or nonexistent. Commonly, the obtainment of these properties is performed through destructive tests such as tensile, impact and fatigue tests. However, the ball indentation technique, a recent methodology to determine mechanical properties of metallic materials, appears as a good alternative. The ball indentation test has the advantage of being a nondestructive test and can be performed in-situ . The ball indentation test is based in multiple indentations at the same place. Thus, with the constant monitoring of the indentation load and depth, a characteristic curve of the assay is determined. Through the correlation between the gotten points from the evaluated curve (stress vs. strain) and the equation-model, it is possible to determine the mechanical properties, such as: yield strength, ultimate tensile strength, hardness, stress x strain curve, strength coefficient and strain hardening exponent. This work highlights the design and development of a control, instrumentation and interfacing system to a ball indentation equipment based on wireless data transmission technology and embedded control by digital signal processors (DSP). The final system will allow the accomplishment of the test quicker, totally automated, safer and accurate.